2022
DOI: 10.53682/jpeunima.v3i2.5308
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perhatian Orang Tua Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Di SMK Negeri 1 Bolaang

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh perhatian orang tua dan motivasi belajar terhadap hasil belajar siswa di SMK Negeri 1 Bolaang. Metode penelitian ini adalah metode kuantitatif dengan sampel 64 orang. Teknik yang digunakan dalam pengumpulan data adalah teknik observasi, kuesioner (angket) dan dokumentasi. Hasil penelitian dianalisis dengan metode analisis regresi ganda, analisis korelasi sederhana dan korelasi ganda. Adapun hasil dari penelitian ini menunjukan (1) Perhatian Orang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The school learning environment is a good place (Wyndham, 2010), and a place to socialize (Fadlilah, 2018;Suherman et al, 2021;Wang et al, 2022). Learning outcomes are also one of the aspects influenced by the learning environment (Mawarsih & Hamidi, 2013;Ramdhani, 2017)". Learning is closely related to literacy.…”
Section: Introductionmentioning
confidence: 99%
“…The school learning environment is a good place (Wyndham, 2010), and a place to socialize (Fadlilah, 2018;Suherman et al, 2021;Wang et al, 2022). Learning outcomes are also one of the aspects influenced by the learning environment (Mawarsih & Hamidi, 2013;Ramdhani, 2017)". Learning is closely related to literacy.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 54.7% is contributed by other variables besides learning independence and attention from parents. Research by (Mawarsih & Hamidi, 2013) The Effect of Parental Attention on Learning Outcomes of … (Furmanissa Okta Dwinanda, Nani Mediatati) showed that there was an influence of parental attention and learning motivation on the learning achievement of Jumapolo State High School students with a Fcount value of 21.117, greater than the Ftable of 3.06. The magnitude of the influence of parental attention and learning motivation on the learning achievement of Jumapolo State High School students is 23.7%, and the remaining 76.3% is influenced by other factors not included in this study.…”
mentioning
confidence: 99%